Model Pewarisan dan Perpetuasi Pengetahuan Pengobatan Tradisional oleh Wong Pinter di Desa Watuaji, Kabupaten Jepara - Muhammad Saputra Agung Pratama; Fadly Husain (Universitas Hamzanwadi, 2026)
Diseases in society are classified into two types: naturalistic diseases, caused by natural factors, and personalistic diseases, caused by supernatural factors. Traditional medicine knowledge is practiced by communities using natural resources in their environment. Personalistic diseases require special treatment by traditional medicine practitioners. This study aims to explore the community's perspective on the existence of Wong Pinter and the model of traditional medicine knowledge transmission carried out by Wong Pinter. The method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and literature studies. The data were analyzed using Cavalli-Sforza and Feldman's Cultural Transmission theory. The results showed that the existence of Wong Pinter in Watuaji Village, Jepara Regency, is still needed by the community to treat illnesses. Wong Pinter has spiritual authority and legitimacy in the community, giving them high social status. The vertical transmission model is obtained orally and experientially from parents or grandparents. Meanwhile, diagonal transmission is obtained from Wong Tuo-tuo and Guru Mursyid. These different transmission sources produce different types of knowledge, namely Ilmu Sapan and Ilmu Bidah. Horizontal transmission is obtained from interactions with peers by passing on collective medical knowledge.